2014
DOI: 10.3389/fpls.2014.00426
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the targeting of a subset of tail-anchored proteins to the outer mitochondrial membrane

Abstract: Tail-anchored (TA) proteins are a unique class of functionally diverse membrane proteins defined by their single C-terminal membrane-spanning domain and their ability to insert post-translationally into specific organelles with an Ncytoplasm-Corganelle interior orientation. The molecular mechanisms by which TA proteins are sorted to the proper organelles are not well-understood. Herein we present results indicating that a dibasic targeting motif (i.e., -R-R/K/H-X{X≠E}) identified previously in the C terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 99 publications
0
34
0
Order By: Relevance
“…Promiscuous TA-mediated targeting to peroxisomes and mitochondria has been observed for only a few Arabidopsis proteins, all of which play a role in fission of both peroxisomes and mitochondria (e.g., FISSION1A [FIS1A] and FIS1B [Zhang and Hu, 2009]; PEROXISOMAL AND MITOCHONDRIAL DIVISION FACTOR1 [PMD1; Aung and Hu, 2011]). Specific targeting to the OMM alone, as observed for the TA of TOM20-4 in this study, has been suggested to be either dependent on a dibasic targeting motif within the TA or on the presence of a TA in combination with upstream protein features and lipid composition of the OMM (Marty et al, 2014). In our study, exclusive targeting of PEN2 to the OMM by replacing the genuine TA with the TA of TOM20-4 was sufficient to restore entry control against nonadapted Bgh conidiospores.…”
Section: Discussionmentioning
confidence: 55%
“…Promiscuous TA-mediated targeting to peroxisomes and mitochondria has been observed for only a few Arabidopsis proteins, all of which play a role in fission of both peroxisomes and mitochondria (e.g., FISSION1A [FIS1A] and FIS1B [Zhang and Hu, 2009]; PEROXISOMAL AND MITOCHONDRIAL DIVISION FACTOR1 [PMD1; Aung and Hu, 2011]). Specific targeting to the OMM alone, as observed for the TA of TOM20-4 in this study, has been suggested to be either dependent on a dibasic targeting motif within the TA or on the presence of a TA in combination with upstream protein features and lipid composition of the OMM (Marty et al, 2014). In our study, exclusive targeting of PEN2 to the OMM by replacing the genuine TA with the TA of TOM20-4 was sufficient to restore entry control against nonadapted Bgh conidiospores.…”
Section: Discussionmentioning
confidence: 55%
“…These proteins are usually localized in the mitochondrial outer membrane with their catalytic domain facing toward the cytosol (Abell and Mullen, 2011). We could not unequivocally confirm the mitochondrial localization of AtTTM2 at the same resolution as AtTTM1 due to low expression levels of AtTTM2 (under its native promoter), but the facts that (1) it was also predicted to be a tailanchored protein (Marty et al, 2014; Fig. 7C) and (2) our analysis of transiently expressed AtTTM2 (under the strong CaMV35S promoter) showed an identical punctate pattern (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 81%
“…S9). This and the fact that Kriechbaumer et al (2009) and Marty et al (2014) also identified AtTTM2 as a tail-anchor protein suggests that AtTTM2 is also localized to the mitochondrial outer membrane.…”
Section: Atttm1 Is Localized To the Mitochondrial Outer Membranementioning
confidence: 86%
“…When the first translation start site in At5g32470 was preceded by its native Kozak translation initiation sequence, the full-length native fusion construct (FL Kozak-N) appeared to localize exclusively to the cytosol, as judged by its diffuse fluorescence pattern distributed throughout the cell ( Figure 7, row 1, left). When preceded by the strong Kozak sequence, however, the full-length construct (FL Kozak-S) exhibited a distinct punctate fluorescence pattern that coincided with that attributable to the mitochondrial marker protein, Cherry-At1g55450 (Marty et al, 2014) coexpressed in the same cell (Figure 7, row 3, left). Similarly, the constructs in which the predicted N-terminal targeting peptide (residues 1 to 44 or 1 to 63), preceded by the strong Kozak sequence, was fused directly to GFP, also localized to Cherry-At1g55450-containing mitochondria (TP44 Kozak-S and TP63 Kozak-S; Figure 7, rows 1 and 2, right).…”
Section: The At5g32470 Protein Localizes To the Cytosol And Potentialmentioning
confidence: 99%
“….). Cells shown were coagroinfiltrated with binary plasmids encoding each fusion construct (diagrammed above the images) along with a Cherry-tagged mitochondrial marker protein (the mitochondrial outer membrane protein At1g55450; Marty et al, 2014). Each row of images corresponds to the fluorescence attributable to (as indicated by labels) the candidate fusion protein (GFP) and the mitochondrial marker (Mito) (green and red, respectively) and the corresponding merged image.…”
Section: ) (B)mentioning
confidence: 99%